Parental phubbing and academic burnout in adolescents: the role of social anxiety and self-control - Yuqian Jiang; Lu Lin; Ronghua Hu (Frontiers in Psychology, 2023)
Based on the limited resource model of self-control, we construct a chain mediation model to examine the relationship between parental phubbing and adolescents’ academic burnout, and whether social anxiety and self-control play a mediating role in it. We used 4 questionnaires to investigate parental phubbing, social anxiety, self-control, and adolescents’ academic burnout among 828 high school students in Wuhu and Huangshan City, Anhui Province, China. The findings indicated that: (1) parental phubbing, social anxiety, and self-control all significantly predict adolescents’ academic burnout directly and (2) parental phubbing could indirectly influence adolescents’ academic burnout through three pathways: the separate mediating effect of social anxiety and self-control, and the chain mediating effect on both. The results of this study help parents understand how their phubbing actions affect adolescents’ academic burnout and the mechanism of action.